Effectiveness of using google sites-based learning media to improve critical and creative thinking abilities of vocational school students - Khusnul Hidayati; Anis Rahmawati; Danar Susilo Wijayanto (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Critical thinking and creative thinking are the main components and important components related to 21st-century skills. Technology is currently very advanced in learning media, so learning is becoming easier and less boring for students. This is supported by global demands that force the education sector to align technical progress with efforts to improve educational standards. One of the sciences and technologies that can be utilized is interactive learning media based on Google Sites. This research was conducted to see the increase in students' ability to think critically and creatively after using Google Sites as a learning media. The research was conducted at the Accounting Department Vocational School in Madiun Regency and Madiun City, East Java. Data collection was carried out by observing critical and creative thinking skills in class, as well as filling out a questionnaire about Google site-based learning media. The research results show that using Google Sites as a learning media for students can improve students' critical and creative thinking abilities. Students' assessments of Google Sites learning media meet the criteria of being very eligible in all aspects. Google Sites can help teachers provide learning resources for students that will help them understand their lessons and activities better.